RELEVANCE OF LABORATORY FUNCTIONS ON GRADUATES’ TECHNOLOGICAL LITERACY: A NON- EXPERIMENTAL DESCRIPTIVE CORRELATIONAL APPROACH - G. Micabalo, Kingie; Abella, Ily E. (International Journal of Scientific Research and Management (IJSRM), 2022)
The advent of laboratory functions inside an institution greatly affects the technological literacy among students' approach to real-life situations. The study aims to determine laboratory functions' relevance to the graduates' technological literacy. The 181 graduate respondents participated in the study on a snowball method in data gathering. Frequency and simple percentage, weighted mean, Chi-Square Test of Independence, and One-way ANOVA were used to treat and interpret the data. The findings revealed that the graduate respondents perceived laboratory functions to a Moderate Extent. It also revealed that graduates' technological literacy in the aspects of knowledge, capabilities, and ways of thinking and acting was perceived to a Moderate Extent. A genuinely huge connection between the degree of selection of laboratory facility capacities and the degree of innovative education was uncovered. Statistical significant differences in the extent of the adoption of laboratory functions, when grouped by its extent of contribution to these functions to attain graduates' technological literacy, were also identified. The study concluded that laboratory functions greatly affect and provide a significant role in graduates' literacy in technology. If more empowerment is given to the institution's laboratory functions, it will create an efficient and effective student resilience in the ever-changing environment of technology approaches.